Measurement of the principal damping components of composite laminates. (15th December 2022) - Mace, T.; Taylor, J.; Schwingshackl, C.W.
Abstract: The prediction of material damping in composite laminate components may allow for the development of lighter component designs, and can be achieved via several techniques. One such example, the modal strain energy (MSE) technique requires a combination of effective strain energy modelling and accurate principal loss factor parameters. Measuring principal loss factors can be very challenging for lightly damped components due to parasitic or 'extraneous' damping sources introduced by the test set-up itself. To ensure high quality input data to the strain energy models an novel damping test procedure has been developed, which allows for mono-harmonic damping parameter extraction via free decay and logarithmic decrements, whilst minimising extraneous dissipation. Improvements over the established impact hammer testing technique could be shown during the validation of the approach. Highlights: Extraneous damping can be minimised with a novel loss factor measurement rig. Application of loss factor parameters improves prediction accuracy in modelling. New set-up allows identification of facets and drawbacks of a novel modelling approach.